ANALYSIS OF FACTORS AFFECTING INTERNATIONAL BANKING ACTIVITIES: A FOCUS ON THE TRANSACTIONS OF ISLAMIC INTERNATIONAL TRADE FINANCING Case Study in XYZ Islamic Bank - Puspita Puspita (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
This research aims to analyze the factors affecting international banking activities,especially the transactions of Islamic International Trade Financing (case studyin XYZ Islamic Bank). Multinomial Logistic regression analysis was used in thisstudy. The independent variable consisted of capability of human resources, customers’ needs of Islamic International Trade Financing (IITF) facilities and product divercification of Islamic International Trade Finance. Meanwhile, the dependent variable was the Islamic International Trade Financing activities at XYZ Islamic Bank. This study used both primary and secondary data where primary data collected from questionnaire survey of 70 respondents and secondary data from various literatures. The result showed that the factor that significantly affected the Islamic International Trade Financing was the custumers’ needs of Islamic International Trade Financing. The other two factors did not significantly affect the Islamic International Trade Financing at XYZ Islamic Bank. The influence of customers in increasing Islamic International Trade Financing at XYZ Islamic Bank was the active customers which had opportunity 6.024 times higher than the passive customers in affecting Islamic International Trade Financing at XYZ Islamic bank. Recommendation from this study is encouraging the consumer to enhance international trade finance transaction to be more recognize the characteristics of XYZ Islamic Bank consumer. This way would be change passive consumer become active consumer.